The Potential of Innovative Financial Tools: Social Impact Bond (SIB) and Sustainable and Responsible Investment (SRI) sukuk, Towards The Sustainable Growth of The Islamic Finance Industry - Syed Azman, Syed Marwan Mujahid; Engku Ali, Engku Rabiah Adawiah (Università degli Studi di Torino, 2016)
The purpose of this paper is to explicate the congruence of innovative financial tools: Social Impact Bond (SIB) and Sustainable and Responsible Investment (SRI) sukuk with the principles of Islamic Finance, and explore their potential contribution towards the sustainable growth of the Islamic finance and societal wellbeing. Using various literature, the paper takes a comparative approach in explaining and relating the two innovative tools with the development of Islamic finance. The paper finds that there is a growing interest in innovative tools such as SIB and SRI sukuk globally. Furthermore, these tools exemplify the spirit of risk-sharing and social responsibility which are the major essences of Islamic finance that are currently missing in practice. The paper provides a reference towards understanding the mechanism and concepts of SIB and SRI sukuk. It also provides insight to the emerging interest in these innovative tools, and assesses the current innovative efforts in the Islamic finance industry. Additionally, it highlights the potential of these tools towards the sustainable growth of the Islamic finance industry through risk-sharing and societal impact. The paper is exploratory and conceptual in nature therefore further empirical studies can be done